339 Challenges and opportunities in developing a companion animal nutrition curriculum for veterinary students. (5th December 2019) - Kitts-Morgan, Susanna E; Lenox, Catherine; Spangler, Dawn
Abstract: Preparing future veterinarians who are knowledgeable and competent in companion animal nutrition presents distinct challenges and opportunities for veterinary educators. Students enter veterinary school from vastly different undergraduate backgrounds, which translates to students with varying degrees of knowledge related to companion animals and nutrition. Oftentimes, nutrition may be overlooked or not emphasized in veterinary curricula, resulting in new graduates who are not able to perform diet assessments for patients. Because nutrition is a fundamental cornerstone of health, veterinary educators have a responsibility to provide veterinary students with the knowledge and skills necessary to be competent in companion animal nutrition. Challenges for veterinary educators in delivering companion animal nutrition curriculum can be broadly categorized as: 1) challenges regarding lack of student knowledge of the petfood industry/companion animal nutrition, 2) challenges in student ability to apply companion animal nutrition skills, 3) challenges in preparing students for communication with clients, and 4) challenges regarding educational resources to teach veterinary students. On the other hand, many opportunities exist for veterinary curricula to incorporate nutrition effectively. These opportunities include, but are not limited to, offering basic and advanced nutrition courses, nutrition labs, and nutrition case studies. To produce veterinarians competent in companion animal nutrition, veterinary educators must identify and overcome the challenges in training veterinary students.